Low-metallicity star formation: from the first stars to dwarf galaxies; proceedings of the 255th Symposium of the International Astronomical Union held in Rapallo (Genova), Italy, June 16 - 20, 2008 - Hunt, Leslie K (Proceedings of the ... symposium of the International Astronomical Union, 2008)
Literaturangaben